2005
DOI: 10.1080/00016350500206660
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in oral health care: administration strategies of general dental practitioners

Abstract: Although recommendations existed, their impact appeared to be limited. This is significant, since the implementation of recommendations is crucial in making clinical practice more effective and in promoting the health of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…A survey in two Swedish provinces reveals that the most frequently prescribed antibiotics to kidney transplanted patients when performing scaling, tooth extraction and root canal treatment are Amoxicillin, Penicillin, Clindamycin [33].…”
Section: Antibiotic Normal Renal Functionmentioning
confidence: 99%
“…A survey in two Swedish provinces reveals that the most frequently prescribed antibiotics to kidney transplanted patients when performing scaling, tooth extraction and root canal treatment are Amoxicillin, Penicillin, Clindamycin [33].…”
Section: Antibiotic Normal Renal Functionmentioning
confidence: 99%
“…Furthermore, barriers such as knowledge, attitudes and habits might exist on the individual level. Previous studies reported that general dental practitioners (GDPs) in Sweden 26 and England 27 to a large extent administer antibiotic prophylaxis to patients with medical conditions such as renal transplants, diabetes and prosthetic joints. Even though there is no evidence for using antibiotic prophylaxis in patients with these medical conditions, GDPs were confi dent in their decisions on administration of antibiotic prophylaxis.…”
Section: Recommendationsmentioning
confidence: 99%
“…In previous studies we have shown that GDPs lack knowledge about which medical conditions and dental procedures should be considered for antibiotic prophylaxis administration according to recommendations. 26 There is a need for revisions of recommendations to be more evidence-based, but signifi cant efforts are also needed to implement recommendations in clinical practice. A successful implementation strategy must fi rst identify potential barriers.…”
Section: Recommendationsmentioning
confidence: 99%
“…Various studies have been carried out to investigate prescription of antibiotics by dentists , not only for the group with CHD. One such study was also conducted among Norwegian dentists .…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, confusion prevails among dental personnel regarding when and for whom antibiotic prophylaxis is indicated . However, a Swedish study from 2008 revealed that general dental practitioners (GDP) exhibited high confidence in their decisions to administer antibiotic prophylaxis .…”
Section: Introductionmentioning
confidence: 99%